Comparative assessment of Texas horned lizard (Phrynosoma cornutum) gut microbiome diversity and composition throughout transition from captivity to wild - Forehand, Cameron R.; Smith, Sierra N.; Nielsen, Forrest; Bauer, Blake; Watters, Jessa L.; Moody, Ray W.; Becker, Daniel J.; Lanier, Hayley; Marske, Katharine; Siler, Cameron (Frontiers in Microbiomes, 2025)
Microbiomes play a key role in the health of animal hosts. To improve conservation translocation programs like headstarting, it is necessary to consider how the structure of these programs impact the host-associated microbiome. Bringing animals into captivity introduces novel diets and environments; however, the extent to which these factors contribute to the structure of the host’s gut microbiome remains poorly understood. Additionally, it is unclear if periods of captivity leave a lasting signature on the host-associated gut microbiome, which could impact individual health and fitness in the long-term. In this study, we repeatedly sampled the gut microbiome of a cohort of headstart Texas horned lizards (Phrynosoma cornutum) throughout their transition from captivity to the wild. We also collected samples of extrinsic microbial communities present in their captive and wild diet and environment. Finally, we sampled the gut microbiome of wild resident lizards to serve as a baseline comparison. Using 16S rRNA microbial inventories, we examined differences in microbial community composition and diversity between pre-release headstart, post-release headstart, and resident lizards of the wild population. Additionally, we assessed the contribution of environmental and dietary microbial communities to the assembly of P. cornutum gut microbiomes in captivity and the wild. Our results suggest captive P. cornutum harbor gut microbiomes that are distinct from their wild counterparts. However, within two-months post-release, the headstart gut microbiome restructures to be indistinguishable from the wild resident microbiome. Microbiomes associated with the captive diet and environment are distinct in beta diversity, but not alpha diversity, from those in the wild. Our results provide important insights into host-associated microbiome dynamics associated with transition from captivity to the wild and can be used to inform conservation translocation practices.